2017
DOI: 10.1038/s41551-017-0080
|View full text |Cite
|
Sign up to set email alerts
|

A fully functional drug-eluting joint implant

Abstract: Despite advances in orthopedic materials, the development of drug-eluting bone and joint implants that can sustain the delivery of the drug and maintain the necessary mechanical strength in order to withstand loading has remained elusive. Here, we demonstrate that modifying the eccentricity of drug clusters and the percolation threshold in ultrahigh molecular weight polyethylene (UHMWPE) results in maximized drug elution and in the retention of mechanical strength. The optimized UHMWPE eluted antibiotic at a h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
84
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(85 citation statements)
references
References 59 publications
1
84
0
Order By: Relevance
“…Drug-eluting polymeric systems with highly eccentric drug clusters prepared using this method can provide sustained drug release, while retaining drug activity and structural properties during consolidation. 16 We confirmed here that bupivacaine could withstand molding conditions and remained structurally intact after molding (Fig. S3).…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Drug-eluting polymeric systems with highly eccentric drug clusters prepared using this method can provide sustained drug release, while retaining drug activity and structural properties during consolidation. 16 We confirmed here that bupivacaine could withstand molding conditions and remained structurally intact after molding (Fig. S3).…”
Section: Discussionsupporting
confidence: 77%
“…We recently showed that ultra-high molecular weight polyethylene (UHMWPE) bearing surface materials, which are used as a part of most articulation pairs in joint replacements, can be loaded with antibiotics via phase separation molding resulting in a sustained antimicrobial effect in in-vitro and in-vivo models of joint infection. 16 In the present study, we hypothesize that non-opioid analgesics, which are incorporated into and delivered from UHMWPE for pain relief can also show antibacterial effect against Staphylococcus aureus, which is the most common pathogen causing PJI. 17 Our approach is based on previous studies demonstrating antibacterial activity of pain medications including opioids, non-steroidal anti-inflammatory drugs, and amide-type local anesthetics.…”
mentioning
confidence: 87%
“…PJI can be treated by means of medical and/or surgical approaches with or without prosthetic retention, but in the more severe cases, resection and amputation may be necessary. 4,6,7 Treatment of patients with acute infection but with a relatively stable implant usually requires preliminary work such as debridement, antibiotic therapy and implant retention (DAIR). 5 An intervention of single or two-stage surgical revision might be prioritised if the DAIR procedure failed.…”
Section: Introductionmentioning
confidence: 99%
“…2 Antibiotics can be delivered to the infected tissues by intravenous systemic administration. 2,[4][5][6] But effective drug infiltration might be restricted by insufficient blood flow in the area concerned. 6 Providing high concentration of antibiotics over a local area seems to resolve this issue.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation